Calcium phosphate coating on dental composite resins by a laser-assisted biomimetic process. Issue 8 (August 2018) - Nathanael, A. Joseph; Oyane, Ayako; Nakamura, Maki; Koga, Kenji; Nishida, Erika; Tanaka, Saori; Miyaji, Hirofumi
Abstract: Objectives: Dental composite resins with better biocompatibility and osteoconductivity have been sought in endodontic treatments. This study aimed to develop a technique to produce the osteoconductive resin surfaces through calcium phosphate (CaP) coating using a laser-assisted biomimetic (LAB) process. Methods: Light-cured, acrylic-based composite resins were used as substrates. The resin substrate was subjected to a LAB process comprising Nd:YAG pulsed laser irradiation in a supersaturated CaP solution. The LAB-processed substrate was immersed for 3 days in a simulated body fluid (SBF) for the preliminary osteoconductivity assessment. Results: After irradiation for 30 min, the resin surfaces were partly coated with a newly formed CaP layer. The coating layer contained hydroxyapatite as the main crystalline phase and the coating coverage depended on the laser wavelength and the type of resin. The LAB-processed CaP-coated surface exhibited apatite-forming ability in SBF. Conclusions: LAB process is effective for CaP coating on light-cured dental composite resins and improving their osteoconductivity. Clinical significance: The LAB process is a potential new tool to create a cementum-like osteoconductive surface on dental composite resins.